Three-year outcomes following 1420 ABO-incompatible living-donor kidney transplants performed after ABO antibody reduction: results from 101 centers - Opelz, Gerhard; Morath, Christian; Süsal, Caner; Tran, Thuong Hien; Zeier, Martin; Döhler, Bernd (Transplantation, 2015)
Background - Reports from experienced centers suggest that recipients of an ABO-incompatible living-donor kidney transplant after reduction of ABO antibodies experience no penalty in graft and patient survival versus ABO-compatible transplants, but confirmation that these results can be widely replicated is lacking. - Methods - Living-donor kidney transplants from ABO-incompatible donors after ABO antibody reduction registered with the Collaborative Transplant Study during 2005 to 2012 were analyzed and compared with (i) a matched group of ABO-compatible transplant recipients and (ii) all ABO-compatible transplants from centers that performed at least five ABO-incompatible grafts during the study period. - Results - One thousand four hundred twenty living-donor ABO-incompatible kidney transplants were analyzed. Three-year death-censored graft survival was virtually identical for ABO-incompatible transplants versus matched and center controls (P = 0.92 and P = 0.60, respectively). Patient survival rates were also similar (P = 0.15 and P = 0.11, respectively). Early patient survival was lower in ABO-incompatible grafts (P = 0.006 vs. matched controls; P = 0.001 vs. center controls) because of a higher rate of early infectious death (P = 0.037 and P < 0.001, respectively). Death-censored graft and patient survival were not significantly affected by induction therapy and anti-CD20 treatment. ABO antibody reduction by column adsorption was associated with similar death-censored graft survival to plasmapheresis. - Conclusion - In this analysis of prospectively collected data from a large series of ABO-incompatible living-donor kidney transplants performed at 101 centers, death-censored graft and patient survival rates were similar to those achieved in ABO-compatible control groups over the same period.